The Impact of Profitability on Earning Management (An Empirical Study on Manufacturing Companies Registered in the Syrian Securities and Markets Authority) (Journal of Hama University, 2024)
The study aims to test the impact of profitability measured by profit margin, return on assets, return on equity, and earnings per share on earnings management as measured by discretionary accruals according to the modified Jones model in Manufacturing companies registered with the Syrian Securities and Financial Markets Authority. To achieve that goal; Secondary data was collected from the annual financial reports of Manufacturing companies registered with the Syrian Securities and Financial Markets Authority and available on the Authority’s official website. The number of these companies reached (4) companies during the period extending between the years 2012-2022, with a total number of views amounting to (44) views and analyzed using SPSS 20.The results showed a statistically significant impact of the profit margin on earnings management, whereas no statistically significant impact was found between return on assets, return on equity and earnings per share on earnings management.
Keywords: earnings management, profit margin, return on assets, return on equity, earnings per share, modified Jones model